2022
DOI: 10.3389/fneur.2022.836842
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Major Depressive Disorder Following Tinnitus: A Population-Based Study

Abstract: Background and PurposeIn this study, we aimed to evaluate the relationship between tinnitus and a subsequent diagnosis of major depressive disorder (MDD) by studying the incidence of both entities.DesignA retrospective cohort study.MethodsData for this observational follow-up study were retrieved from the Taiwan's National Health Insurance Dataset. A total of 375,272 patients with newly diagnosed tinnitus (study group) were retrieved. The date of first diagnosis of tinnitus was assigned as their index date. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Major depressive disorder (MDD) is a major contributor to disability in the world ( Filatova et al, 2021 ), with an estimated lifetime risk of 20% ( Lin et al, 2022 ). Previous studies reported that the prevalence of MDD in college students was higher (5.9%) than that in the general population (3.4%) ( Auerbach et al, 2016 ; Huang et al, 2019 ) and seemed to increase gradually ( Acharya et al, 2018 ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is a major contributor to disability in the world ( Filatova et al, 2021 ), with an estimated lifetime risk of 20% ( Lin et al, 2022 ). Previous studies reported that the prevalence of MDD in college students was higher (5.9%) than that in the general population (3.4%) ( Auerbach et al, 2016 ; Huang et al, 2019 ) and seemed to increase gradually ( Acharya et al, 2018 ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%